Evaluation of Hospital Management Information Systems in Research Units Using the PIECES Method - Gamasiano Alfiansyah; Mudafiq Riyan Pratama; Selvia Juwita Swari; Iqbal Rhamadhan Suryawiyanto; Faizatun Nikmah (Universitas Muhammadiyah Yogyakarta, 2022)
Technological advances have an impact on health services, one of which is the use of hospital management information systems in the research unit of the Dr Sardjito hospital. However, the implementation of the system encountered obstacles, including the absence of notification of the maximum loan limit and the absence of case classification based on disease in the borrowed medical record file. The purpose of the study was to evaluate the hospital management information system in the research unit. This research was a qualitative research with respondents 3 officers in the research unit. Data collection through in-depth interviews and observation. Data were analyzed using content analysis method. The results showed that the system does not have a notification if the number of files borrowed exceeds the maximum limit, the system produces loan data and medical record return data accurately, but the system can be accessed simultaneously on different computers. This study suggests to hospitals to add a notification feature if the number of files borrowed exceeds the maximum limit and add a medical record borrowing feature based on disease classification.